Viable Sweetpotato Technologies in Africa (VISTA) Tanzania project - International Potato Center (2015)
VISTA Tanzania got underway with diagnostic studies, setting up multiplication in 41 farmers groups, and conducting Trainer of trainers’ courses for 31 extension personnel. All is set to go for the coming year